Pengaruh Influencer Marketing dan Ulasan Pelanggan Terhadap Keputusan Pembelian Produk Skincare The Originote di Shopee - Alia Candra Devi; Citra Savitri; Syifa Pramudita Faddila (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The current high number of internet users makes digital marketing an important aspect for companies in promoting products. Marketing strategies using influencers have become a popular method in this digital era. Many consumers now tend to seek information from content shared by influencers and reviews from previous customers when making purchasing decisions. This study aims to determine the influence of influencer marketing and customer reviews on purchasing decisions for The Originote products. This research uses quantitative methods and followers of the @theoriginoteofficial account are the population of this research. Purposive sampling technique was used to take a research sample of 384 respondents. Data collection used Google forms and data analysis with SEM-PLS with the help of SmartPLS 4 software. The results of this research show that influencer marketing and customer reviews have a positive and significant influence on purchasing decisions for The Originote skincare products.